Does the gastroprotective action of a medicinal plant ensure healing effects? An integrative study of the biological effects of Serjania marginata Casar. (Sapindaceae) in rats - Périco, Larissa Lucena [UNESP]; Heredia-Vieira, Silvia Cristina [UNESP]; Beserra, Fernando Pereira [UNESP]; Santos, Raque de Cássia dos; Weiss, Marcio Barczyszyn [UNESP]; Resende, Flavia Aparecida [UNESP]; Ramos, Matheus Aparecido dos Santos[UNESP]; Bonifácio, Bruna Vidal [UNESP]; Bauab, Taís Maria [UNESP]; Varanda, Eliana Aparecida [UNESP]; Gobbi, Juliana Irani Fratucci de[UNESP]; Rocha, Lúcia Regina Machado de[UNESP]; et al. (Elsevier B. V., 2015)
Serjania marginata (Sapindaceae), a medicinal plant commonly found in the Brazilian Cerrado, Paraguay, Bolivia and Argentina, is also known as cipó-uva or cipó-timbó. Ethnopharmacological studies indicate that the leaves from this medicinal plant are used in folk medicine to treat gastric pain. The overall objective of this study was to evaluate the gastroprotective and healing effect of the hydroalcoholic extract obtained from S. marginata (HESM) leaves using rodent experimental models. As part of the integrative study of this medicinal plant, we also evaluated the acute toxicity, antimicrobial, antidiarrheal, (anti)mutagenic, and hemodynamic effects. We performed a pharmacological study to test the acute toxicity and antimutagenic effect (Ames assay) of the HESM. The HESM was tested against different necrosis-promoting agents and experimental manipulations, such as absolute ethanol, cysteamine, pyloric ligature, and ischemia-reperfusion (I/R) injury. The gastroprotective effect of the HESM was assessed by analyzing the gastric juice (volume, pH, total acidity) and the mucus in the gastric mucosa from rats. We assessed the levels of NO, sulfhydryl compounds, PGE2, vanilloid receptor, glutathione (GSH), and malondialdehyde (MDA), as well as the myeloperoxidase (MPO) activity. The gastric healing effects of the HESM were evaluated during 7 or 14 days of treatment. The intestinal motility, antidiarrheal action, and antibacterial effects (microdilution methods) of the HESM were also evaluated. The phytochemical analysis of the HESM revealed the presence of saponins, flavonoid glycosides, and tannins. The extract exhibited no sign of acute toxicity or mutagenic effect in vitro. In contrast, this extract exhibited a protective effect against the mutagenic action of direct- and indirect-acting mutagens. Only the oral administration of HESM (250mg/kg) significantly decreased the severity of gastric damage induced by ethanol (60.13%) and I/R (58.31%). The HESM exerts its gastroprotective effects by decreasing the MPO and MDA activities in the gastric tissue and by increasing the amount of adherent mucus covering the gastric mucosa. In vitro, the extract also displayed evident antimicrobial effects against Helicobacter pylori. However, the preventive effect of the HESM was not accompanied by an ulcer-healing effect. The treatment with HESM (14 days) significantly increased gastric lesions in 99% of the tested animals compared with the control group. This result represents a highly relevant piece of evidence that should resonate as an alert against the chronic use of this medicinal plant as an antiulcer in folk medicine. Despite the anti-H. pylori and gastroprotective actions of S. marginata in experimental models, the gastric injuries aggravation induced after chronic treatment with the HESM argues against the use of this plant species in folk medicine.
Keywords: Antimicrobial activity; Antimutagenic effect; Gastroprotective effect; Sapindaceae; Serjania marginata casar